EDUKASI KELUARGA BERENCANA DALAM MENDUKUNG KESEHATAN IBU DAN ANAK DI WILAYAH RW 06 KELURAHAN BENCAH LESUNG - Aulia, Nur (PITIMAS: Journal of Community Engagement in Health, 2025)
Family Planning (FP) is one of the government's efforts to control population growth and improve maternal and child health. Low public knowledge about the importance of FP can affect participation in the use of contraceptives. This activity aims to increase public knowledge about the Family Planning program through health education activities. The activity was conducted by administering a pre-test to determine the initial level of residents' knowledge, followed by counseling on the benefits, types, and importance of FP, and concluded with a post-test to measure the increase in knowledge. Based on the evaluation results, out of 14 people, the number of those with good knowledge increased from 3 people before the counseling to 12 people after the counseling. This indicates an increase in public knowledge following the FP education activities. Health education on Family Planning is effective in increasing public knowledge and can be used as a promotive effort in the field of reproductive health.